Cytotoxic effect of potato aspartic proteases (StAPs) on Jurkat T cells - Mendieta, Julieta Renee (2009)
StAPs are potato aspartic proteases with cytotoxic activity against plant pathogens and spermatozoa. StAPs cytotoxic activity is selective, since these proteins do not exert toxic effect on plant cells and erythrocytes. In this work, we investigated the capacity of StAPs to exert cytotoxicity on human leukaemia cells. Obtained results show that StAPs induce apoptosis on Jurkat T cells after a short time of incubation in a dose-dependent manner. However, no significative effect on the T lymphocytes viability was observed at all StAPs incubation times and concentrations tested. These results suggest that StAPs can be conceptually promising leads for cancer therapy.